Appetite-suppressing effects and interactions of centrally administered corticotropin-releasing factor, urotensin I and serotonin in rainbow trout (Oncorhynchus mykiss) - Ortega, Van A.; Lovejoy, David A.; Bernier, Nicholas J. (Frontiers in Neuroscience, 2013)
Corticotropin-releasing factor (CRF), urotensin I (UI) and serotonin (5-HT) are generally recognized as key regulators of the anorexigenic stress response in vertebrates, yet the proximal effects and potential interactions of these central messengers on food intake in salmonids are not known. Moreover, no study to date in fishes has compared the appetite-suppressing effects of CRF and UI using species-specific peptides. Therefore, the objectives of this study were to (1) assess the individual effects of synthesized rainbow trout CRF (rtCRF), rtUI as well as 5-HT on food intake in rainbow trout, and (2) determine whether the CRF and serotonergic systems interact in the regulation of food intake in this species. Intracerebroventricular (icv) injections of rtCRF and rtUI both suppressed food intake in a dose-related manner but rtUI [ED50 = 17.4 ng/g body weight (BW)] was significantly more potent than rtCRF (ED50 = 105.9 ng/g BW). Co-injection of either rtCRF or rtUI with the CRF receptor antagonist α-hCRF(9–41) blocked the reduction in food intake induced by CRF-related peptides. Icv injections of 5-HT also inhibited feeding in a dose-related manner (ED50 = 14.7 ng/g BW) and these effects were blocked by the serotonergic receptor antagonist methysergide. While the anorexigenic effects of 5-HT were reversed by α-hCRF(9–41) co-injection, the appetite-suppressing effects of either rtCRF or rtUI were not affected by methysergide co-injection. These results identify CRF, UI and 5-HT as anorexigenic agents in rainbow trout, and suggest that 5-HT-induced anorexia may be at least partially mediated by CRF- and/or UI-secreting neurons.